LEGAL PROCEDURE IN RELATION TO CONTEMPT OF COURT - ภูตลาดขาม, กฤษณ์; อินทมาโน, นิสิต (Journal of Roi Et Rajabhat University, 2018)
In Thailand, the act constituting the contempt of court is explained in the Civil Procedural Code section 30 to 32 and section 33 allows a judge to punish a person who commits contempt of court by ordering him to go outside the courtroom, by imprisoning him for less than 6 months or by fining him for less than 500 Baht or both. Therefore, the provision of the contempt of court is provided as same as the criminal law. However, the legal procedure of contempt of court is not provided in the Civil Procedural Code or any other rules, leading to many discussed issues. Firstly, the contempt of court is the offence against the state, so the affected individual cannot demonstrate the evidence to the court and has a limited right to appeal. Secondly, the affected judge can punish the accused for contempt of court occurring outside the court, so this may cause the unfair judgment. Thirdly, the court can start its proceeding without the presence of the accused and the accused does not be allowed to defend himself or to appoint a lawyer. Fourthly, there is a limitation for appealing in case the contempt of court occurs in high court, especially in the Supreme Court. And lastly, if the court punishes the accused for the contempt of court which also violates the criminal law, the court can repunish him in criminal case and the accused can be imprisoned again. The contempt of court is the special provision, different from a criminal procedure and a civil procedure. There should be the specific provision of its procedure to balance the power and freedom of the court and the right and liberty of the accused as same as the defendant in a criminal case.